The effect of percentage carbonon the CVD coating of plain carbon and low alloy steels - Hailu, Wekianos (Zede Journal of Ethiopian Engineers and Architects, 2023)
Two steels En 3 and En 39 were given a TiC-TiN CVD coating in the carburized and uncarburized conditions. The continuity of the coatings and their adherance to the substrate were examined. The thickness of the deposited coatings were also measured, their adherence to the substrate and their thickness was off ected by the percentage carbon of the substrates surf ace. Moreover it was found out that there exists a marked difference between the coatings deposited on the two steels.